The first experience of pulmonary valve perforation with concomitant arterial duct stenting in patients with pulmonary atresia and intact interventricular septum - Maksymenko, A. V.; Kuzmenko, Y. L.; Dovhaliuk, A. A.; Motrechko, O. O.; Vitovska, O. R. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Pulmonary atresia with intact interventricular septum (PAIVS) – is a complex congenital heart disease characterized by a valve atresia with attendant right ventricle (RV) and a tricuspid valve (TV) hypoplasia of varying degrees with duct-dependent pulmonary circulation. One of the modern methods of treating PAIVS is pulmonary valve perforation with subsequent arterial duct stenting. Purpose – to present first experience of the PV perforation with concomitant arterial duct stenting in patients with PAIVS. Materials and methods. Three neonates with PAIVS were performed concomitant PV perforation with arterial duct stenting in UCCC. Results and discussion. The procedure was successful in three newborn patients with moderate RV hypoplasia with a membranous PV atresia with IVS. On average, after intervention, patients were in the ICU for 5 days, two of them needed ventilatory support, one – sympathomimetic support. The median length of hospital stay was 13 days. Postoperative compli-cations were not observed. There was no early mortality. Conclusions. PV perforation with concomitant arterial duct stenting is an effective and safe method for optimizing pul-monary circulation in patients with PAIVS with moderate RV hypoplasia.